Industry Participation in Curriculum Development and in the preparation and implementation of study programs at Higher Learning Institutions in East Africa - Niyonzima, Eliezer; Edoru, John Michael; Gierszewska , Wioleta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
The core mission of higher learning institutions is to produce graduates having desired skills to contribute to the socio-economic development of their countries. However, in the East Africa, the industry is not satisfied with the quality of graduates from the higher learning insti tutions. A similar problem occurs in other parts of the world, including Central and Eastern Europe. The problem under investigation therefore is to establish whether those institutions in East Africa involve the industry in curriculum development and delivery. Study aimed at investigating the ways in which higher learning institutions collaborated with industry to ensure that the students get relevant skills aligned to the needs of the labour market. Quantitative data was collected through an online questionnaire among 350 academic middle level managers in 35 universities from 7 countries of the East African community. Criteria for selecting the research sample: random selecting universities. The East African Community countries (Burundi, Democratic Republic of Congo, Kenya, Rwanda, South Sudan, Uganda, Tanzania). Somalia was not included in the study. The study revealed that higher learning institutions in the East African Community had links with industry but this was mostly limited to written agreements but with few concrete actions. Respondents (31%) claimed that the industry was involved in curriculum development. Higher learning institutions should enhance practical partnerships with industry by establishing formal mechanisms like offices in charge of linkage with industry and regular fora. These institutions should particularly involve industry in all stages of curriculum development and in activities of curriculum delivery.